Digital nomadism as a new form of remote work for companies : a first evaluation of the business idea of a digital nomad platform - Syrbe, Sören (2022)
Digital nomadism, an enhanced form of remote work that combines work with travel and leisure, has become increasingly popular in the course of the COVID pandemic. With nearly twice as many digital nomads now permanently employed by companies (MBO Partners, 2021), it is important to examine how this work model affects employee performance and well-being. This master’s thesis hypothesizes that if digital nomadism has positive effects on employee performance and well-being, managers would be willing to integrate it into their companies. To support this integration, the author proposes a digital nomad platform. In the course of this master thesis, the business idea is subjected to a first evaluation. An online questionnaire was applied for empirical research, and data from 115 managers were collected and analyzed using structural equation modeling. The findings show that managers believe that digital nomadism can have a positive impact on employee well-being, which in turn would be a reason for them to adopt it. The findings also show that managers have doubts about whether the proposed digital nomad platform is useful enough. From the results, it can be concluded that there is a great deal of interest in the idea of introducing digital nomadism into corporate structures. However, the actual business idea of the digital nomad platform still needs to be further validated with the help of a prototype.